Effects of oral and intramuscular vitamin K prophylaxis on PIVKA-II assay parameters in breastfed infants in Turkey - Uluşahin, Namdar; Arsan, Saadet; Ertogan, Fadıl (The Turkish Journal of Pediatrics, 1996)
Protein induced by vitamin K absence (PIVKA-II) has been used for the evaluation of vitamin K deficiency in the newborn. Differing PIVKA-II detection rates in various studies on hemorrhagic disease of the newborn have not been explained satisfactorily. In this study we investigated the PIVKA-II values of 44 healthy breastfed infants, of whom 29 received vitamin K1 either orally (N=13) or intramuscularly (n=16), and the remaining 15 constituted the control group. PIVKA-II was detected in 15.3 percent (2/13) of the oral and 25 percent of the (4/16) intramuscular group on the third day of life. The detection rate was 93.3 percent (14/15) in the control group. However, at the one-month follow-up, there were no PIVKA-II positive infants. In conclusion, PIVKA-II positivity among breastfed Turkish infants on the third day of life was high compared to that in other studies, perhaps due to a delay in enzyme maturation related to racial, environmental and nutritional factors.
Keywords: vitamin K1; neonate; PIVKA-II; hemorrhagic disease